Light touch, lean tally: Impacts of an MSME support program in Côte d'Ivoire - Tabea Lakemann; Bernd Beber; Jann Lay; Jan Priebe (German Institute of Global and Area Studies (GIGA), 2024)
In many developing countries, micro, small, and medium enterprises (MSMEs) employ more people than any other type of firm, so identifying ways to raise productivity, improve employment conditions, and formalize labor in these settings is of prime policy importance. However, due to the small number of workers per firm and the possibly long results chain linking management to employment, few MSME-targeted interventions and evaluations address job-related outcomes directly. We do so in a randomized controlled trial (RCT) of a support program for MSMEs in Côte d'Ivoire that included financial management and human resources (HR) components. Six and 18 months after the end of the program, we find muted impacts on business practices, access to finance, and firm performance. On the employment side we find positive and significant impacts on job quality, driven by the share of employees receiving at least the minimum wage and the share with written contracts. We find no significant effect on the number of staff. Taken together, our results underscore the difficulty of boosting firm performance and creating jobs with a low-intensity intervention on the one hand, and the feasibility and importance of improvements in employment quality in MSMEs in developing countries on the other.
Keywords: O12; L26; M10; 330; Côte d'Ivoire; MSME support; employment quality; firm performance; randomized controlled trial